Peran Citizen Journalism Dalam Pemberitaan Bencana Palu Di Cnn Indonesia - Ahmad Abdiyansyah; Ummu Kalthum Binti Abdul Hadi Awang (Wardah, 2019)
Abstract: This research entitled "The Role of Citizen Journalism in Palu Disaster Reporting on CNN Indonesia". Natural disasters that took place in Palu, Central Sulawesi, became a sorrow for Indonesia. This disaster has completed the settlement and eliminated the lives of our brothers. Documentation that spreads in online media results from spontaneous recording of victims. The emergence of the phenomenon of citizen journalism in disaster news has become commonplace in Indonesia. The rapid development of citizen journalism took place in 2004 a tsunami compilation in Aceh which was covered by the victims themselves. Direct news from victims can beat the news made by professional journalists. In fact, videos made by residents when the event was aired by all television stations. The video was recorded by Cut Putri, regarding the seconds of the December 26, 2004 Tsunami compilation, and is considered an important milestone in the development of citizen journalism in Indonesia. Citizen Journalism in Palu, Central Sulawesi. By using a qualitative descriptive method, namely by analyzing the contents of the news contained on the CNN Indonesia Youtube channel where ordinary citizens participate in it. Using Holsti's analysis theory which analyzes data to answer the statement "what, for whom, and how and draw conclusions." The results of the study show that citizen journalism contributes to the value of the news presented in the news. By discussing and discussing what happened during the disaster. However, the quality of recordings from amateurs is not very good, in this case online news media still uses amateur citizen recordings to be published to viewers as supporting data from data approved by professionals. In conditions like this, online news media, especially CNN Indonesia, prioritize more than quality. Keywords: Role, citizen journalism, online journalism, disaster news